To Determine the Frequency of Central Obesity in Acute Coronary Syndrome Patients Presenting to a Cardiac Care Health Facility - Elahi, Noor; Saghir, Tahir; Anees, Neelam; Jameel, Sabar; Hussain, Kinza; Khan, Farhan; Taha, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Central obesity, characterized by excessive fat accumulation in the abdominal region, is a major risk factor for cardiovascular diseases. Unlike general obesity assessed by body mass index (BMI), central obesity has been shown to have a stronger correlation with acute coronary syndromes (ACS) due to its association with insulin resistance, inflammation, and endothelial dysfunction. Objective: To determine the frequency of central obesity among patients presenting with acute coronary syndrome (ACS) at a tertiary cardiac care facility in Karachi, Pakistan. Methods: This descriptive cross-sectional study was conducted at the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD), Karachi. A total of 370 patients with ACS were enrolled using non-probability consecutive sampling. Waist-hip ratio (WHR) was measured, and central obesity was defined as WHR >0.90 for males and >0.85 for females. Data on demographics, comorbidities, and anthropometrics were collected via structured questionnaire. Results: The overall prevalence of central obesity was 60.3 percent among ACS patients. A higher frequency was observed in females (75.7%) compared to males (50.0%). Central obesity was significantly associated with female gender (p < 0.001), hypertension (p = 0.02), and family history of obesity (p = 0.016). Multivariate logistic regression showed that female gender (OR = 2.74), hypertension (OR = 1.65), and family history of obesity (OR = 1.89) were independent predictors of central obesity. Conclusion: It is concluded that central obesity is common among patients with acute coronary syndrome, especially in females. These findings highlight the need for routine assessment of waist-hip ratio in cardiac care settings and support the development of targeted strategies to reduce central obesity in high-risk populations.